Solar UV Radiation in Saint-Denis, La Réunion and Cape Town, South Africa: 10 years Climatology and Human Exposure Assessment at Altitude - (:unkn) unknown (My University, 2019)
Solar ultraviolet radiation (UVR) monitoring is important since it depends on several atmospheric parameters which are associated with climate change and since excess solar UVR exposure and has significant impacts on human health and wellbeing. The objective of this study was to investigate the trends in solar UVR during a decade (2009-2018) in Saint-Denis, Reunion Island (20.9°S, 55.5°E, 85 m ASL) and Cape Town, South Africa (33.97°S, 18.6°E, 42 m ASL). This comparison was done using total daily erythema exposure as derived from UVR sensors continuously at both sites. Climatology over the 10-year period showed extreme UVR exposure for both sites. Slight changes with opposite trends were found, +3.6% at Saint-Denis and −3.7% at Cape Town. However, these two sites often experience extreme weather conditions thereby making the trend evaluation difficult. Human exposure assessment was performed for hiking activities at two popular high-altitude hiking trails on the Maïdo-Grand Bénare (Reunion) and Table Mountain (Cape Town) with a handheld radiometer. Extreme exposure doses of 64 SED and 40 SED (Standard Erythemal Dose, 1 SED = 100 J.m −2) were recorded, respectively. These high exposure doses highlight the importance of raising public awareness on the risk related to excess UVR exposure at tourist sites, especially those at high altitude.
Keywords: African Research